2012 IEEE International Conference on Virtual Environments Human-Computer Interfaces and Measurement Systems (VECIMS) Proceedin 2012
DOI: 10.1109/vecims.2012.6273184
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of SSVEP based BCI with Emotiv EPOC

Abstract: In recent years, steady-state visual evoked potential (SSVEP) based brain-computer interface (BCI) has received much attentions. However, most SSVEP based BCI devices are not portable and have high price, which are not suitable to be used for clinical and commercial purpose. Thanks to the low cost and portable Emotiv EPOC, it brings BCI into daily life. In this paper, SSVEP based BCI through Emotiv EPOC is implemented. BCI 2000 is employed to connect Emotiv EPOC and Matlab to implement the online system. The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(62 citation statements)
references
References 12 publications
3
57
0
2
Order By: Relevance
“…The EEG signals have a poor signal to noise ratio [19] which makes the brain activity patterns difficult to be detected. Nevertheless, it is not always possible to discriminate between the different mental tasks.…”
Section: Mec Methods Ameliorationmentioning
confidence: 99%
“…The EEG signals have a poor signal to noise ratio [19] which makes the brain activity patterns difficult to be detected. Nevertheless, it is not always possible to discriminate between the different mental tasks.…”
Section: Mec Methods Ameliorationmentioning
confidence: 99%
“…One of the most consumer-oriented devices is the neuroheadset Emotiv Epoc+ (Liu et al, 2012;Duvinage et al, 2013), shown in (Figure 3A), which includes 14 electrodes distributed in the four lobules (Lang, 2012) electrode configuration shown ( Figure 3B). In this paper, we compare the Epoc+ with the actiCAP (V-Amp and Easy Cap) from Brain Products, see (Figure 3C) with electrode configuration shown in (Figure 3D).…”
Section: Selection Of the Bmi Systemmentioning
confidence: 99%
“…However, ease of use and affordability come at the price of reduced signal quality. Still, a comparative analysis of SSVEP data acquired from EPOC and medical-grade EEG found that the data acquired from EPOC is reliable [32], although the authors cautioned that the Emotiv should not be used for medically serious cases [12]. The radio connection is also a limitation, but studies have shown its reliable use in realtime applications [22].…”
Section: State Of the Artmentioning
confidence: 99%